An improved approach to the subcontracting procurement process in a lean construction setting - Yin, Samuel Yen-Liang; Tserng, H. Ping; Toong, Shih Ning; Ngo, Thanh Long (Journal of Civil Engineering and Management, 2014)
The subcontracting procurement process is one of the most important issues impacting the costs of engineering projects and construction projects, in particular. Traditional procedures of subcontracting procurement tend to limit the opportunities for price negotiation and cooperative relationships between contractors and neglect potential issues such as engineering interface, construction risk, and waste. Based on case studies of construction projects, we propose a “lean” subcontracting procurement process (LSPP) drawing from lean construction theory. The process consists of a novel Seven-Arrangement operation plan and four types of standard operating flows. Not only does the proposed LSPP help sub-contractors eliminate various types of waste in construction projects, it also establishes a common information platform and cooperative environment that help participating contractors understand the work emphasis of each operation and the whole operation in sequence. As a result, the relationships between participating contractors become cooperative, potential risks in construction projects can be discovered early, and profits are shared between contractors. Thus, this process allows contractors to obtain long-term benefits.